Garcinia mangostana pericarp and α-mangostin normalized the expression of colonic and renal cytochrome P450 genes and abated the expression of renal inflammatory genes in dextran sulfate sodium-induced ulcerative colitis in mice - Naroeporn Nopwinyoowong, Waranya Chatuphonprasert, Nitima Tatiya-Aphiradee, Kanokwan Jarukamjorn (Journal of Applied Pharmaceutical Science, 2023)
Ulcerative colitis (UC) causes inflammation and ulceration in the colon and often develops renal manifestation. Garcinia mangostana pericarp crude extract (GM) and α-mangostin (MGS), a major bioactive compound, have potentiality to consider as a new complementary therapy for UC due to pharmacological activities, particularly anti-inflammatory activity. However, safety in terms of drug interaction has been neglected. The current study investigated the impacts of GM and MGS on the cytochrome P450 (CYP) profiles in the mouse colon and kidneys, including the inflammatory response in the kidneys. Male ICR mice were orally pre-treated with 40–1,000 mg/kg/day of GM, 30 mg/kg/day of MGS, or 100 mg/kg/day of sulfasalazine daily for 7 days. On days 4–7, 6 g/kg of 40 kDa dextran sulfate sodium (DSS) was orally administrated to induce UC. RT-qPCR was performed to determine the mRNA expressions of CYP and inflammatory genes. DSS suppressed Cyp1a1, Cyp2b9/10, Cyp2c29, Cyp2d9, Cyp2e1, Cyp3a11, and Cyp3a13 expressions, whilst GM and MGS positively adjusted the CYP expression in both organs. Besides, Tnf-α, Mcp-1, and Nf-κb expressions were up-regulated after UC induction, while they were restored to the level comparable to the control by GM and MGS. Therefore, G. mangostana pericarp is a promising candidate to normalize the CYP profiles and reducing the risk of drug interaction, and to revitalize against inflammation.
Keywords: Mangosteen, DSS, drug-interaction, anti-inflammation, extraintestinal manifestation